2022
DOI: 10.1039/d2ta06099j
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer regulated by domain differences between host and guest donors in ternary organic solar cells

Abstract: A clear selection rule for the third component is the premise for improving the efficiency of ternary organic solar cells (T-OSCs), which is also the top priority for clarifying the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The general AMBER force field (GAFF) uses 33 basic atom types and 22 special atom types covering almost all chemical spaces consisting of H, C, N, O, S, P, F, Cl, Br, and I . Based on more than thousands of optimizations and single-point calculations by researchers, it has been verified as a complete force field, available for all parameters of the basic atom types. , At present, it is widely used in the theoretical study of OSCs using GAFF for MD of the donor and acceptor, and the obtained data are consistent with the quantum calculations, which verifies the reliability of GAFF. Taking the acceptor as an example, the dihedral angles of acceptors obtained from MD results were concentrated around the lowest potential energy range of the DFT scanned structures shown in Figure S1 in the Supporting Information. In terms of atomic charge fitting, the constrained electrostatic potential (RESP) fitting method solves the problems of conformational dependence as well as numerical instability of internal atomic charges and atomic equivalence well, and GAFF with RESP charges can better describe the intra- and intermolecular interactions .…”
Section: Theoretical Calculationsmentioning
confidence: 75%
“…The general AMBER force field (GAFF) uses 33 basic atom types and 22 special atom types covering almost all chemical spaces consisting of H, C, N, O, S, P, F, Cl, Br, and I . Based on more than thousands of optimizations and single-point calculations by researchers, it has been verified as a complete force field, available for all parameters of the basic atom types. , At present, it is widely used in the theoretical study of OSCs using GAFF for MD of the donor and acceptor, and the obtained data are consistent with the quantum calculations, which verifies the reliability of GAFF. Taking the acceptor as an example, the dihedral angles of acceptors obtained from MD results were concentrated around the lowest potential energy range of the DFT scanned structures shown in Figure S1 in the Supporting Information. In terms of atomic charge fitting, the constrained electrostatic potential (RESP) fitting method solves the problems of conformational dependence as well as numerical instability of internal atomic charges and atomic equivalence well, and GAFF with RESP charges can better describe the intra- and intermolecular interactions .…”
Section: Theoretical Calculationsmentioning
confidence: 75%
“…However, the charge transfer process accompanied by charge recombination, and the competition between the two processes, will result in very different PCEs of OSCs. It was reported that the donor and acceptor arrangement could be face-on, edge-on and slipped in donor/acceptor interfaces, and the face-on interfaces make the largest contribution to the charge transfer [46,48,49]. In this work, the interface models extracted from the final equilibrium system with a face-on style are mainly considered, which normally have good intermolecular π-π stacking (shown in Figure S6).…”
Section: The Charge Separation and Recombination At The D/a Interfacementioning
confidence: 99%
“…In addition, the distribution in the region of 01-301 of the dihedral angle of PTB7-Th/IEICO -PM6/Y6 -PTB7-Th/ITIC -PTB7-Th/IEICO-4F This journal is © The Royal Society of Chemistry 2024 -PTB7-Th/IT-4F -PM6/IT-4F gradually increases, which corresponds to a face-on stacking orientation. 17 So more face-on stacking in the compounded morphology could increase the probability of energy inversion, which indicates that the probability of energy inversion is directly affected by the D/A stacking.…”
mentioning
confidence: 99%
“…15 Besides, Δ E 3 is related to the film morphology of the donor/acceptor (D/A) blend, including D/A stacking distance and stacking orientation. 16,17 In this sense, the elucidation of CT characteristics is likely to achieve the goal of loss reduction.…”
mentioning
confidence: 99%